From b1f5c3f8d6671b4331cef1dcebdf63b7a43a3a2b Mon Sep 17 00:00:00 2001 From: priyanka Date: Wed, 24 Jun 2015 15:03:17 +0530 Subject: initial commit / add all books --- 632/CH2/EX2.8/example2_8.sce | 15 +++++++++++++++ 1 file changed, 15 insertions(+) create mode 100755 632/CH2/EX2.8/example2_8.sce (limited to '632/CH2/EX2.8/example2_8.sce') diff --git a/632/CH2/EX2.8/example2_8.sce b/632/CH2/EX2.8/example2_8.sce new file mode 100755 index 000000000..9b038f4d4 --- /dev/null +++ b/632/CH2/EX2.8/example2_8.sce @@ -0,0 +1,15 @@ +//clc() +//kG = (6.7 * 10^-4) * (( G * (ds + dt) / ds)^0.8) / ((ds^0.4)*(dG^0.2)) +//kG - lbmol/(h ft^2 atm), G - lb/(ft^2 h), ds, dG, dt - feet +//kG1 - kmol/(m^2 h atm), G1 - kg/(m^2 h), ds1, dG1, dt1 - m +G = 0.2048;//G1 * lb/(ft^2 h) +d = 3.2808;//d1 * ft +ds = d; +dt = d; +dG = d; +kG = 4.885;//kG1 (lbmol/(h ft^2 atm) = 4.885 * kmol/(m^2 h atm)) +C = (6.7 * 10^-4) * (( G * d / ds)^0.8) / ((ds^0.4)*(dG^0.2))* kG; +disp(C,"Co-efficient = ") +// this is the constant for the equation +// the equation thus becomes, +// kG1 = C * (( G1 * (ds1 + dt1) / ds1)^0.8) / ((ds1^0.4)*(dG1^0.2)) -- cgit